A new bright eclipsing hot subdwarf binary from the ASAS and SuperWASP surveys - Schaffenroth, Veronika; Geier, Stephan; Drechsel, Horst; Heber, Ulrich; Wils, P.; Ostensen, R. H.; Maxted, P. F. L.; Di Scala, G. (Astronomy & Astrophysics, 2013)
We report the discovery of a bright (mV = 11.6 mag), eclipsing, hot subdwarf binary of spectral type B with a late main sequence companion from the All Sky Automated Survey (ASAS 102322-3737.0). Such systems are called HW Vir stars after the prototype. The lightcurve shows a grazing eclipse and a strong reflection effect. An orbital period of P = 0.13927 d, an inclination of i = 65.86, a mass ratio q = 0.34, a radial velocity semiamplitude K1 = 81.0 km s-1, and other parameters were derived from a combined spectroscopic and photometric analysis. The short period can only be explained by a common envelope origin of the system. The atmospheric parameters (T eff = 28 400 K, log g = 5.60) are consistent with a core helium-burning star located on the extreme horizontal branch. In agreement with that we derived the most likely sdB mass to be MsdB = 0.46 M ⊙, close to the canonical mass of such objects. The companion is a late M-dwarf with a mass of Mcomp = 0.16 M⊙. ASAS 102322-3737.0 is the third brightest of only 12 known HW Virginis systems, which makes it an ideal target for detailed spectroscopic studies and long-term photometric monitoring to search for period variations, e.g., those caused by a substellar companion. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: eclipsing; Binaries: spectroscopic; Stars: early-type; Stars: fundamental parameters; Stars: individual: ASAS 102322-3737.0; Subdwarfs